2018
DOI: 10.1016/j.nicl.2018.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological fMRI: Effects of subanesthetic ketamine on resting-state functional connectivity in the default mode network, salience network, dorsal attention network and executive control network

Abstract: BackgroundSubanesthetic dosages of the NMDAR antagonist, S-Ketamine, can cause changes in behavior in healthy subjects, which are similar to the state acute psychosis and are relevant in translational schizophrenia research. Functional magnetic resonance imaging (fMRI) can be used for non-hypothesis-driven analysis of brain connectivity. The correlation between clinical behavioral scores and neuroimaging can help to characterize ketamine effects on healthy brains in resting state.Methodseventeen healthy, male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 29 publications
6
37
5
Order By: Relevance
“…We assessed drug modulations of the RSNs for each pipeline. Ketamine reduced connectivity within all networks (Figures 4 and 6b), unlike some previous research where no changes within the VN (Niesters et al, 2012) and DMN (Mueller et al, 2018;Niesters et al, 2012) were found.…”
Section: Ketaminecontrasting
confidence: 80%
See 3 more Smart Citations
“…We assessed drug modulations of the RSNs for each pipeline. Ketamine reduced connectivity within all networks (Figures 4 and 6b), unlike some previous research where no changes within the VN (Niesters et al, 2012) and DMN (Mueller et al, 2018;Niesters et al, 2012) were found.…”
Section: Ketaminecontrasting
confidence: 80%
“…We assessed drug modulations of the RSNs for each pipeline. Ketamine reduced connectivity within all networks (Figures and b), unlike some previous research where no changes within the VN (Niesters et al, ) and DMN (Mueller et al, ; Niesters et al, ) were found. Reductions similar to those found with our SIMPLE pipeline within the DMN were also found by Bonhomme et al (): these authors used two dosing levels, with the lowest being most similar to ours, and their preprocessing like our SIMPLE pipeline.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…However, this technique is unable to estimate the dynamic connectivity among the cortical regions. The functional Magnetic Resonance Imaging (fMRI) technique is widely utilized to characterize the cortical FC [10-12] as it provides excellent spatial resolution. However fMRI has relatively lower temporal resolution [13,14] (slow sampling rate; ∼1s).…”
Section: Introductionmentioning
confidence: 99%